Eco-Anxiety:Right to Healthy Environment - Siti Hafsyah Idris; Norjannah Nasution (Universitas Airlangga, 2022)
Eco-anxiety' as a concept is relatively new and has received media attention recently, even though the feeling has probably existed for some time. People who are depressed and lose control when thinking about the impact of human activity on the planet, such as climate change. Climate change is an actual dimension into their mental-health problems, which is not medically recognised or defined. This is normative legal research. The data were consolidated and examined using the legal norm method, which uses qualitative legal analysis, logic, and argumentation. This paper reviewed the literature on eco-anxiety and its legal implications. Environmental and health law continues to be separate bodies of international law, even though the right to health is intertwined with the right to a healthy environment. A right to a clean and healthy environment should explicitly include the right to health-physically and mentally. Priority should be given to greening public health infrastructure, such as mental health facilities, as part of eco-anxiety recovery plans to support the emergence of the environmental impact on mental health and the country's mental health promotion and prevention efforts to serve their needs better.